Effectiveness and safety of metoclopramide in treatment of intractable hiccup: a protocol of systematic review and meta-analysis - Tao Chen; Long Wang; Changyan Zi; Yongxiang Gao; Die Wang; Baocheng Zhang; Baojia Wang (BMJ Open)
Introduction Hiccup is a common disease that not only occurred on adults but also on infants, which can severely do harm to patients’ physical and psychological health. Metoclopramide has been reported to have effects on intractable hiccup. However, there is a limited evidence that describes the efficacy and safety of metoclopramide in the treatment of intractable hiccup. The aim of this article is to obtain evidence on the effectiveness and safety of metoclopramide in treating patients with intractable hiccup.Methods and analysis We will search the following databases, including PubMed, Cochrane Library, Embase, Web of Science, CBM, Wan-fang, VIP database, CNKI and MEDLINE from their inception to 11 November 2021. All the randomised controlled trials associated with metoclopramide in treating intractable hiccup will be included. Articles screened, selected and extracted will be performed by two researchers independently. The risk of bias will be assessed by using the Cochrane Collaboration. We will carry out the meta-analysis by using RevMan V.5.4 software.PROSPERO registration number CRD42021293000.